India: World-Class Universities? - Altbach, Philip G.; Salmi, Jamil (International Higher Education, 2017)
India’s higher education and research sectors have been generally underfunded, especially in view of the tremendous growth in numbers of students. Compared to the other BRIC countries, the percentage spent on education, 4.1 percent of GDP, is second to Brazil. This article explores the Indian higher education system with respect to its potential to create world-class universities.